The relationship between big five personality and quality of life of people with disabilities: The mediating effect of social support - Cai, Lin; He, Jiaxin; Wu, Yibo; Jia, Xuji (Frontiers in Psychology, 2023)
Objective The quality of life of people with disabilities is of great significance to social stability and development. Increasing the quality of life among the disabled has become a worldwide topic. This study aims to examine the relationship between the big five personality and quality of life and the mediating effects of social support indicators in people with disabilities. Methods This was a cross-sectional study with 358 people with disabilities (193 women and 165 men). A questionnaire was utilized to measure big five personality, social support, and quality of life variables. Pearson’s correlation analysis and structural equation modeling were used to examine the relation among big five personality, social support, and quality of life. Results QOL was positively correlated with social support (r = 0.402, p < 0.001), extraversion (r = 0.324, p < 0.001), agreeableness (r = 0.474, p < 0.001), conscientiousness (r = 0.482, p < 0.001), and openness (r = 0.498, p < 0.001). QOL was negatively correlated with neuroticism (r = −0.186, p < 0.001). The mediating effect of social support on the relationship between neuroticism and the quality of life of people with disabilities was not significant. Social support significantly mediated the relationship between extraversion, agreeableness, conscientiousness, openness, and quality of life. Overall, positive personality traits (extraversion, agreeableness, conscientiousness, and openness) in the Big Five Personality of people with disabilities could increase their quality of life by Perceiving social support. But social support could not significantly mediate the relationship between neuroticism and the quality of life of people with disabilities. Conclusion These new findings suggest that combining individual factors (personality) and environmental factors (social support) can better improve the quality of life of people with disabilities.